Determinants of Economic Gains from Crop Production in Africa: The Case of Smallholder Group Farmers in the Democratic Republic of Congo - Birachi, Eliud Abucheli; Ochieng, D.; Owuor, G.; Buruchara, Robin Arani; Ochieng, J.; Mapatano, S. (International Center for Tropical Agriculture, 2011)
Measures to alleviate poverty among smallholder farmers in Africa have focused on individual farmers all through the 21st century. However, these have not yielded much success, forcing research and development organizations to focus their efforts on technological innovations and other interventions through farmer groups. The potential gain in productivity through group interventions is a major factor underlying the need for developing countries to promote groups. Group actions are analyzed within the concept of collective action. Based on the new institutional economics approach, collective efforts solve societal problems, and focus on the conditions under which groups of people with common interests choose to act to achieve their respective interests (Clague, 1997). The farmer groups fill some of the gaps generated by this situation for example in input and output marketing.